Imaging of HIV-1 envelope-induced virological synapse and signaling on synthetic lipid bilayers. - Prins, K; Vasiliver-Shamis, G; Cammer, M; Depoil, D; Dustin, M; Hioe, C (2012)
Human immunodeficiency virus type 1 (HIV-1) infection occurs most efficiently via cell to cell transmission(2,10,11). This cell to cell transfer between CD4(+) T cells involves the formation of a virological synapse (VS), which is an F-actin-dependent cell-cell junction formed upon the engagement of HIV-1 envelope gp120 on the infected cell with CD4 and the chemokine receptor (CKR) CCR5 or CXCR4 on the target cell (8). In addition to gp120 and its receptors, other membrane proteins, particularly the adhesion molecule LFA-1 and its ligands, the ICAM family, play a major role in VS formation and virus transmission as they are present on the surface of virus-infected donor cells and target cells, as well as on the envelope of HIV-1 virions(1,4,5,6,7,13). VS formation is also accompanied by intracellular signaling events that are transduced as a result of gp120-engagement of its receptors. Indeed, we have recently showed that CD4(+) T cell interaction with gp120 induces recruitment and phosphorylation of signaling molecules associated with the TCR signalosome including Lck, CD3ζ, ZAP70, LAT, SLP-76, Itk, and PLCγ(15). In this article, we present a method to visualize supramolecular arrangement and membrane-proximal signaling events taking place during VS formation. We take advantage of the glass-supported planar bi-layer system as a reductionist model to represent the surface of HIV-infected cells bearing the viral envelope gp120 and the cellular adhesion molecule ICAM-1. The protocol describes general procedures for monitoring HIV-1 gp120-induced VS assembly and signal activation events that include i) bi-layer preparation and assembly in a flow cell, ii) injection of cells and immunofluorescence staining to detect intracellular signaling molecules on cells interacting with HIV-1 gp120 and ICAM-1 on bi-layers, iii) image acquisition by TIRF microscopy, and iv) data analysis. This system generates high-resolution images of VS interface beyond that achieved with the conventional cell-cell system as it allows detection of distinct clusters of individual molecular components of VS along with specific signaling molecules recruited to these sub-domains.